EMPOWERING LANGUAGE TEACHERS THROUGH ACTION RESEARCH: TWO CASE STUDIES FROM MALAYSIA - Kuang Ching Hei; Maya Khemlani David (University of Kuningan, 2017)
Given the easy availability of information due to social media, it is generally recognized that language teachers need to transform themselves from being mere disseminators of information to that of innovators. Literature suggests that to do so, language teachers should make action research an indispensable part of their language teaching armory. This paper aims to encourage language teachers to take charge of their own profession by conducting action research in their respective classrooms. The paper illustrates two case studies which stress on the process which can be duplicated by teachers as well as the outcome which can be used for improvement and for sharing with peers through publication. By engaging in action research, language teachers can move beyond their conventional teaching roles to become researchers cum practitioners who are able to rise to the occasion by overcoming current language issues first hand instead of taking advice from educational researchers. Keywords: action research, language teaching, reflection